2017
DOI: 10.4102/hts.v73i3.4344
|View full text |Cite
|
Sign up to set email alerts
|

The role of spirituality as a coping mechanism for South African traffic officers

Abstract: Traffic officers are faced with many stressful situations, yet each traffic officer might cope differently with these stressors. Spirituality is regarded as an essential defence in stressful situations. Therefore, this article provides a basic framework guiding traffic officers and practitioners, on how spirituality can be used as a coping mechanism when faced with various work-related stressors. An interpretative, qualitative study was conducted utilising purposive sampling in which 10 traffic officers partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Internal police corruption is a challenge to public trust, cohesion of departmental policies, human rights and legal violations involving serious consequences. Police corruption can take many forms, such as (l) Corruption of Authority, (2) Kickbacks, (3) Opportunistic Theft, (4) Shakedowns, (5) Protection of Illegal Activities, (6) The Fix, (7) In July 2013, the Philippine National Police (PNP) was ranked as the most corrupt institution in the Philippines, according to a survey by the Global Corruption Barometer of the anti-corruption watchdog Transparency International. Alexis Romero wrote in the Philippine Star, "The survey showed that 69 percent of surveyed Filipinos believed police personnel were corrupt, 64 percent believed public officials and civil servants were affected by corruption, while 58 percent had the same view on political parties.…”
Section: Introductionmentioning
confidence: 99%
“…Internal police corruption is a challenge to public trust, cohesion of departmental policies, human rights and legal violations involving serious consequences. Police corruption can take many forms, such as (l) Corruption of Authority, (2) Kickbacks, (3) Opportunistic Theft, (4) Shakedowns, (5) Protection of Illegal Activities, (6) The Fix, (7) In July 2013, the Philippine National Police (PNP) was ranked as the most corrupt institution in the Philippines, according to a survey by the Global Corruption Barometer of the anti-corruption watchdog Transparency International. Alexis Romero wrote in the Philippine Star, "The survey showed that 69 percent of surveyed Filipinos believed police personnel were corrupt, 64 percent believed public officials and civil servants were affected by corruption, while 58 percent had the same view on political parties.…”
Section: Introductionmentioning
confidence: 99%